2007
DOI: 10.1103/physrevd.76.023508
|View full text |Cite
|
Sign up to set email alerts
|

Probing the coupling between dark components of the universe

Abstract: We place observational constraints on a coupling between dark energy and dark matter by using 71 Type Ia supernovae (SNe Ia) from the first year of the five-year Supernova Legacy Survey (SNLS), the cosmic microwave background (CMB) shift parameter from the three-year Wilkinson Microwave Anisotropy Probe (WMAP), and the baryon acoustic oscillation (BAO) peak found in the Sloan Digital Sky Survey (SDSS). The interactions we study are (i) constant coupling δ and (ii) varying coupling δ(z) that depends on a redshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
317
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(346 citation statements)
references
References 111 publications
26
317
3
Order By: Relevance
“…The addition of a non-linear function of the Ricci scalar R to the Einstein-Hilbert action has been demonstrated to cause acceleration for a wide variety of f (R) functions [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a non-linear function of the Ricci scalar R to the Einstein-Hilbert action has been demonstrated to cause acceleration for a wide variety of f (R) functions [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,…”
Section: Introductionmentioning
confidence: 99%
“…The lower b 2 , the closer the evolution of the Universe to a non-interacting model is. It should be emphasized that this phenomenological description has proven viable when contrasted with observations, i.e., SNIa, CMB, large scale structure, H(z), and age constraints [8,9,14,18], and recently in galaxy clusters [16,17].…”
mentioning
confidence: 99%
“…Indeed, it was shown that the coupling is small but positive which indicates that DE may decay into DM. Nevertheless, albeit the interaction hypothesis is gaining ground the observational limits on the strength of the coupling remain weak [18].…”
mentioning
confidence: 99%
“…In order to do this the model must successfully reproduce some important cosmological scenarios considered before in standard cosmology. For example, FRW cosmologies filled with a single fluid ρ with equation of state p = ωρ have an energy density of the form ρ = ρ 0 a −3(ω+1) , and those with two non-interacting fluids, as we have seen above, have the energy densities given by (7). Another type of FRW cosmologies, which provides us with a way to approach the coincidence problem, has energy densities which scale exactly as powers of the scale factor, so they are considered to be given by ρ 1 = ρ 10 a α and ρ 2 = ρ 20 a β in order to have ρ 1 /ρ 2 ∼ a const .…”
Section: Field Equations For Two Fluid Componentsmentioning
confidence: 99%